Knowledge and Attitudes on Preventing and Treating Dentin Hypersensitivity and Its Predicting Factors: A Cross-sectional Study with Brazilian Citizens - Mosquim, Victor; Carneiro, Gabriela Utrago; Foratori-Junior, Gerson Aparecido; Honório, Heitor Marques; Gillam, David Geoffrey; Wang, Linda (European Journal of Dentistry, 2022)
Objectives Most dental schools have included dentin hypersensitivity (DH) as part of their taught curriculum to educate undergraduates; however, it is possible that the public still does not recognize its symptoms and the factors that predispose to the onset of this condition. Thus, the aim of this study was to assess the knowledge of a Brazilian population regarding the prevention and treatment of DH and to identify what self-reported factors can serve as predictors of the frequency of DH.Materials and Methods An online questionnaire investigated the demographic characteristics, oral health self-perception and attitudes, and DH prevention and treatment measures of 226 participants.Statistical analysis Data were analyzed descriptively and by a multiple linear regression with DH frequency score as the dependent variable (α < 0.05).Results Total 61.1% of females (n = 138) and 38.9% of males (n = 88) (mean age: 35.1 ± 12.2 years) completed the questionnaire. The sample's mean DH frequency score (minimum 0; maximum 20) was 4.2 and classified as low, with 19.1% using desensitizing products and 22.1% reporting having noncarious cervical lesions (NCCLs). When experiencing DH episodes, 21.2% never and 30.1% rarely scheduled dental appointments. Regression analysis retrieved a significant final model (F [5,220] = 12.047; p < 0.001; R2 = 0.215).Conclusion This study identified that 36.7% and 18.6% of the sample were unaware that DH can be both prevented and treated, respectively. Moreover, the presence of NCCLs, frequency of daily toothbrushing, use of desensitizing products, presence of DH modulating factors, and the presence of parafunctional habits symptoms served as predictors of DH frequency.
Keywords: dentin hypersensitivity; patient; health; questionnaire; regression analysis; surveys